A rare case of recurrent pregnancy loss associated with high-titer positivity for perinuclear anti-neutrophilic cytoplasmic antibodies - Akhila Vasudeva; Raviraja V Acharya; Pratap Kumar (Journal of Human Reproductive Sciences, 2012)
We present a case of recurrent pregnancy loss associated with unusual constellation of utoimmunity-related features such as hypertension, severe hrombocytopenia, hypothyroidism and persistent high titers of perinuclear antineutrophilic cytoplasmic antibodies. Her clinical features did not fit into a particular diagnosis of vasculitides, systemic lupus erythematosis (SLE) or other known autoimmune diseases where this autoantibody is found in high titers. We report the unusual association of this autoantibody with recurrent early fetal demise in this case.